A retrospective study of serous ovarian tumour with IHC correlation: a three-year study - Manoja Vaddadi; Ali Baqher Hussaini Syed; Jyothi V; Shamoon Sulthana; Florence Nightingale; Priyatham Gundla; Purnima Sirisha Gattim (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Serous ovarian tumors account for 40% of all ovarian cancer cases and remain a major cause of cancer-related mortality in women due to late-stage diagnosis. This retrospective study aimed to analyze the clinicopathological features of serous ovarian tumors and their correlation with immunohistochemical (IHC) markers, including WT-1, CA-125, CK-7, CK-20, and CEA, to improve diagnostic accuracy and prognostic evaluation. Materials & Methods: The study included pathology data from August 2020 to July 2023, focusing on patients with ovarian neoplasms. Clinical characteristics were correlated with IHC markers. Results: Results showed that 62% of tumors occurred in women of reproductive age, with abdominal pain being the most common symptom (62%). The majority (88%) of tumors were benign, while 8% were malignant and 4% were borderline. Most tumors (88%) were unilateral, and the predominant tumor size ranged from 6 to 10 cm. High-grade serous carcinomas were identified in two cases, exhibiting Ki-67 labeling indices of 26–50% and >50%, respectively. Ki-67 expression was significantly higher in malignant tumors (50%) compared to borderline tumors (26%) (p < 0.001). IHC analysis showed strong WT1 nuclear expression, CK7 cytoplasmic expression, and CA125 membrane staining in serous ovarian cancer cases. CK20 and CEA were negative in all cases of serous adenocarcinoma. Malignant tumors exhibited significantly higher Ki-67 expression than borderline tumors. Conclusion: The study concluded that increasing age, postmenopausal status, bilaterality, and complex tumor morphology were associated with malignancy risk. The use of IHC markers such as WT1, CK7, CK20, CEA, and CA125 remains essential for accurate diagnosis and differentiation of serous ovarian tumors.